Transient painful bullous dermatosis of childhood. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
A case of self-healing within two months autoimmune bullous dermatosis in a 5-year-old baby giri was reported. The clinical features, the histological and immunofluorescence studies led to a presumptive diagnosis of seborrheic pemphigus. However, the spontaneous healing within two months and the lack of responsible drugs did not support this diagnostic hypothesis. The Author proposed the diagnosis of transient painful bullous dermatosis of childhood.